Screening for Postpartum Depression by Hospital-Based Perinatal Nurses. Issue 6 (November 2018) - Logsdon, M. Cynthia; Vogt, Krista; Davis, Deborah Winders; Myers, John; Hogan, Felicia; Eckert, Diane; Masterson, Katlin
Abstract: Purpose: The primary purpose of this study was to evaluate acceptability by new mothers of postpartum depression (PPD) screening and education about community resources by hospital-based perinatal nurses. A secondary purpose was to determine further screening for PPD that women received by community providers in the first few weeks after birth. Methods: The study design was descriptive. As per standard practice on the unit, all new mothers were screened for depression the night before hospital discharge using the Edinburgh Postnatal Depression Scale (EPDS). New mothers identified as high risk for depression by EPDS scores greater than or equal to 10 ( n = 75) and a comparison group of mothers at low risk for depression with EPDS scores less than 10 ( n = 26) were recruited from an academic health sciences center. Participants were contacted by telephone 2 to 4 weeks later and asked about the acceptability of screening for depression and education about community resources by hospital-based perinatal nurses, as well as if they had received further screening for depression by community providers. Descriptive and correlational statistics were used to analyze data. Results: The majority of new mothers found it acceptable to be screened for depression and educated about community resources by hospital-based perinatal nurses. Many new mothers were not asked about depressive symptoms by community providers. There was no significant correlation between demographics and depression risk. Clinical Implications: New mothers viewed depression screening and receiving information on community resources as a positive part of their care. Communication between inpatient and community caregivers should be improved so that new mothers can benefit from seamless depression assessment, evaluation, and treatment. Abstract : Postpartum depression is the most common complication of childbirth, affecting 10% to 15% of new mothers. In this study, hospital-based perinatal nurses screened women prior to discharge from the hospital after birth for postpartum depression and followed up with a telephone call several weeks later. Women were receptive to the screening and follow-up calls. Nurses are in an optimal position to screen for postpartum depression and make sure women get appropriate and timely referral and treament.